Cultivating Urban Storytellers: A Radical Co-Creation to Enact Cognitive Justice for/in Self-Built Neighbourhoods - Catalina Ortiz (Urban Planning, 2022)
We all carry an imperative to imagining collectively more just cities, to engaging more meaningfully with multiple urban actors and their different sensibilities through their stories. Storytelling helps to foster empathy, to understand the meaning of complex experiences, and, most importantly, to inspire action. With the rise of the digital era and new technologies at hand, we have an opportunity to redefine not only the way we tell, connect, and engage with our collective stories, but also how we work together in forming them. Based on the research design project Patrimonio Vivo | Living Heritage, grounded in the city of Medellín, this article illustrates the dynamics and potentials of co-creation with cultural organizations and creative teams through learning alliances. Our alliance among a cultural community centre, a cooperative of architects, a grassroot organisation and post-graduate students around the world used storytelling to propel an ecology of urban knowledges. Working online during the global lockdown, we mobilised stories of solidarity, care, memory, and livelihoods through the narrative of people, places, and organisations following their trajectories as the basis for the design of spatial strategies. This collaborative work aimed at contributing to the recognition of everyday spatial practices in self-built neighbourhoods as a form of “living heritage” of the city and a key building block for reframing a more progressive “integral neighbourhood upgrading” practice. I argue that using storytelling as a co-creative methodology, based on learning alliances, we can bridge the ecology of urban knowledges to foster cognitive justice and transform the current stigmatizing urban narrative of self-built neighbourhoods.